An Extension of the Hilbert's Integral Inequality. (27th September 2009) - Yu, Zhou; Xuemei, Gao; Mingzhe, Gao
Abstract : It is shown that an extension of the Hilbert's integral inequality can be established by introducing two parametersm ( m ∈ N ) andλ ( λ > 0 ) . The constant factors expressed by the Euler number andπ as well as by the Bernoulli number andπ, respectively, are proved to be the best possible. Some important and especial results are enumerated. As applications, some equivalent forms are given.